Permissive, Authoritarian, and Authoritative Parenting Style and Smartphone Addiction on University Students - Hifizah Nur; Putri Setyaningrum; Annisa Novandita (Universitas Ahmad Dahlan, 2021)
This research was conducted to find the correlation between permissive, authoritative, authoritarian parenting styles with smartphone addiction. This study involved 225 students of one private university in Jakarta from various faculties (67 male and 158 female) selected based on a non-probability sampling method - convenience sampling. The measuring instruments used in this study were the Smartphone Addiction Scale (SAS) developed by Kwon et al. (2013) and the Parenting Style scale developed by Baumrind (1971), and the personal information form used to collect sample personal data. The quantitative analysis of the research was carried out using the Pearson product-moment test, Spearman correlationâ€™s test, descriptive test, t-test, and ANOVA test of difference. This study's results were there is a significant correlation of 0.320 between permissive parenting style and smartphone addiction, also there is a significant correlation of 0.300 between authoritarian parenting and smartphone addiction. Furthermore, there is no significant relationship between authoritative parenting and smartphone addiction.Â Keywords: Smartphone Addiction, Permissive Parenting Style, Authoritarian Parenting Style.Â